Prevalencia y factores de riesgo asociados a fasciolosis en niños de 3 a 12 años que se atienden en el Hospital Julcán, La Libertad, Perú 2018 - Paredes Sandoval, Junner Perlix (2019)
The present study was conducted to determine the prevalence of human fasciolosis in children from 3 to 12 years of age who were treated at the Hospital Julcán in the period from July to October 2018. The consent of the father of the family was requested so that the child could participate in the work of investigation. He was given two collector flasks to collect two stool samples on two consecutive days. He was interviewed with the epidemiological clinical file of the MINSA to look for data on risk factors associated with the disease. Stool samples were subjected to Direct Examination and then the Rapid Sedimentation Technique for the search for Fasciola hepatica eggs. The positive samples were referred to the Reference Laboratory of La Libertad for confirmation of parasitological diagnosis and egg count by the Kato Katz technique. A blood sample from the minor was requested for an immunological confirmation by the IgG Immunoblot technique in the Reference Laboratory. No cases of infant fasciolosis were found in the urban area of the town of Julcán. In rural areas, the prevalence of infant fascioliasis in the Yellow sector was 6.9%, in Red 4.7% and in Green 11.1%. On average in the rural area it was 5.2%, being determined as a mesoendemic zone. The egg count for the three sectors of the rural area ranged from 48 to 168 hgh, with infection intensities being mostly mild to moderate. There were no significant differences in relation to sex and age group: The associated risk factors in the rural area were: drinking tap water, consumption of short-stemmed vegetables, raising cattle or sheep around the house and defecating in the air free.